Potency of probiotic therapy for dental caries prevention - Indah Listiana Kriswandini (Dental Journal (Majalah Kedokteran Gigi), 2008)
Probiotic therapy is one of the therapies to prevent dental caries prospectively. Such therapy has been used in the medical area but not in dentistry. Probiotic therapy is important to be done since this therapy study ecosystem in oral cavity which has many commensal bacteria more detail. The probiotic material used to prevent dental caries is the microorganism which counter microorganism causing dental caries and its virulent product (acid lactic). Veillonella sp. use lactic acid as the end product of S. mutans which cause the dental caries. The principle of probiotic therapy is the comensalism symbiosis found in oral cavity ecosystem. Veillonella sp could be added to anticipate the lactic acid which cause enamel demineralization. Hopefully dentist will apply probiotic therapy, so there will be more study of Veillonella sp. as probiotic material for dental caries prevention. Further research on Veillonella sp in probiotic therapy and Immunology need to be done to achieve the balance of ecosystem.